Direct measurement of electron Bernstein waves in Low Aspect ratio Torus Experiment (LATE). (26th January 2022) - Guo, Xingyu; Ashida, Ryo; Noguchi, Yuto; Kajita, Ryusuke; Tanaka, Hitoshi; Uchida, Masaki; Maekawa, Takashi
Abstract: By using a newly developed five-pin probe antenna and two-dimensional mechanical probe driving system, the 2D wave pattern of phase and amplitude has been directly measured in the Low Aspect ratio Torus Experiment (LATE) device, for an overdense ECR plasma with microwave obliquely injected. In the case of O-mode injection, an electron Bernstein wave (EBW)-like wave pattern has been detected for the first time, in a localized region near the upper hybrid resonance layer. The pattern has a short wavelength of about 2 mm and is also electrostatic and backward. In the case of X-mode injection, the 2D wave pattern is quite different and no EBW signal can be observed. By adjusting the toroidal magnetic field in O-mode injection, it is found that both the position and size of the EBW region have changed, which suggests the localized condition of efficient O-X-B conversion and high collisional damping rate of EBWs in these experiments.